BUSINESS FEASIBILITY AND STRATEGY OF BUSINESS DEVELOPMENT OF CATFISH HATCHERY IN MINAPOLITAN AREA OF MAGELANG DISTRICT - Riyadi Tri Cahyono; Any Suryantini; Jangkung Handoyo Mulyo (Universitas Gadjah Mada, 2019)
This study aims to (1) identify the feasibility of catfish hatchery business and (2) to know the alternative and strategic priorities that can be applied in the development of catfish hatchery business in the Minapolitan Area of Magelang District. Research location in sub-District of Muntilan, Mungkid, and Sawangan, was chosen by purposive sampling. Respondents were chosen by snowball 42 as samples from farmers and stakeholders related to catfish hatchery business. Data analysis used on the business feasibility is BEP and R/C ratio criteria. The analysis of business development strategy uses SWOT analysis. The business feasibility analysis tool used is cost analysis, revenue, and nett revenue. Feasibility analysis result obtained BEP revenue of Rp53.587.484,00, BEP production of 255.087,71 unit fish, BEP price of Rp 56.00 per unit fish, and R/C ratio of 1,67. The development of strategy of catfish hatchery business are (1) maintaining good relationship with stakeholders and maximizing natural resources management for business development due to low interest of community on catfish hatchery business, and (2) utilizing expert resources (practitioners and academics) in the field of hatchery by government assistance to improve the quality of seed products and for expanding market size to meet the increased demand.